Discussion Of The Paper Of A. L. Jones (Rocky Mountain Coal Mining Institute, 1923)
PRESIDENT WHITESIDE: The chair will now throw the meeting open to discussion. GEO. B. PRYDE: In the old days at Rock Springs we had electric plants situated about half a mile from our mines; we had small boiler plants; we had an electric plant with about 600 kilowatt capacity. About ten years ago we discarded the old steam plants and started building towards a centralized power plant. We now have three 2,500-kilowatt turbine generators and one 1,000, and our peak load is about 7,000 kilowatts. We have had to rebuild the old power plant, scrap the old machines, and install water tube boilers. We did this as a matter of economy in a small local plant we had years ago, and it has grown to be a large central plant, supplying power for about 20,000 tons of coal daily, and distributing this power within a radius of twenty miles. We have found this method of power to be more economical than with the old plants, and the people who buy power from us in the Rock Springs field say it has been to their advantage also. We found this last year, when we had to shut down for five months, that that plant was the only plant operating in the Rock Springs field, supplying all the power, running of fans and pumping during the time the mines were shut down, and it helped the situation very much. We had an old wooden building which we had to tear down, raise the walls, and put on a steel roof; had to rebuild the boiler room and rebuild the boilers. The water situation at Rock Springs has never been very good; we get our water from wells 250 to 500 feet deep, and use one and one-quarter million gallons a week. We have two large spray ponds and we have gotten along well. There isn't any comparison between the central power station and the old method of making power. (Applause.) FRANK YOUNG: I listened with a great deal of pleasure to the paper just read, and it struck me it was remarkable how a paper prepared by anyone could be so nearly identical and coincide so very near with the experience of another. It is just like some work I have had. I had the engineering part to do for the power plant for ten years, and I think at that time we did all of the things that he mentioned in his paper. Also his analysis of the cost of power seems to me exactly right. If I had gathered the figures and made the statement myself I think it would have been very much the same as was read. The recommendation that it is better to buy